CYCLOTOMIC CLASSES IN THE NORMING DECODING BCH-CODES - D. N. Hoang; V. K. Konopelko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Norming decoding based on cyclotomic classes with main and subordinate norms is exanimated. It was found that all the norms of BCH codes and their error vector generators are the parts of complete cyclotomic classes. Identification of the error vectors generators with serial and parallel-serial processing of combined cyclotomic classes is proposed.